Hepatoprotective Therapy Efficacy in Obstructive Hepatobiliary Diseases: A Prospective Randomized Study - Maksymenko, Mykhailo; Kulivets, Olexii; Havryliuk, Roman; Zukow, Walery (Journal of Education, Health and Sport, 2025)
Introduction and purpose Obstructive diseases of the hepatobiliary system present a complex set of clinical challenges characterized by impaired bile outflow and progressive hepatocellular damage. Despite significant advances in interventional and surgical approaches, liver dysfunction associated with these disorders continues to substantially impact patient morbidity and mortality. Hepatoprotective agents have emerged as a potential adjunctive therapeutic strategy, although their efficacy in managing hepatobiliary obstruction remains insufficiently investigated. The purpose of our article was to assess the efficacy and clinical feasibility of hepatoprotective therapy in obstructive hepatobiliary diseases. Materials and methods A prospective randomized cohort study was conducted from 2020 to 2024 at the Surgical Department №2 of the Kyiv Municipal Clinical Hospital of Emergency Medical Care, analyzing the treatment results of 139 patients with obstructive biliary disease (54 men, 85 women). Patients were randomly stratified into two groups: a control group receiving standard conservative therapy and a hepatoprotective therapy group receiving supplementary treatment with Remaxol, Silymarin, and S-adenosylmethionine for 21 consecutive days. Results Biochemical parameter analysis revealed significant improvements in patients receiving combined hepatoprotective therapy compared to the control group. On day 7, patients administered hepatoprotectors demonstrated a 46.7% decrease in total bilirubin (reducing to 111.2±22.1 μmol/L), compared to a 39.5% decrease (to 128.0±23.5 μmol/L) in the control group (p<0.05). Liver enzyme levels exhibited a more pronounced improvement in the hepatoprotector therapy group, with alanine aminotransferase (ALT) decreasing from 175±25 U/L to 52±5 U/L (a 70.3% reduction) on day 7, contrasted with a 45.6% decrease in the control group (from 182±22 U/L to 99±10 U/L) (p<0.001). Cholestatic markers also demonstrated superior responsiveness to hepatoprotective therapy. Alkaline phosphatase (ALP) decreased by 53.4%, and gamma-glutamyl transpeptidase (GGTP) decreased by 60.0% after 7 days, compared to decreases of 44.0% and 23.1% in the control group, respectively (p<0.01 for both parameters). By day 21, both groups exhibited significant improvement; however, the hepatoprotective therapy group maintained statistically significant advantages across all parameters (p<0.01), particularly in transaminase normalization (ALT: 31±3 U/L vs. 66±8 U/L, p<0.001; AST: 25±5 U/L vs. 61±3 U/L, p<0.001). Conclusions The implementation of hepatoprotectors facilitates a statistically significant acceleration in the normalization of liver function biochemical indicators, specifically bilirubin, transaminases, and cholestasis markers. The most pronounced differentiation was observed in the reduction of ALT and AST (p<0.001), which indicates a substantial mitigation of cytolytic syndrome under hepatoprotective intervention. An integrated therapeutic approach incorporating hepatoprotectors for obstructive hepatobiliary diseases enables more rapid restoration of hepatic functional status and potentially mitigates the risk of complications. Based on the obtained data, the protocol demonstrated particular effectiveness in transaminase normalization (ALT: 31±3 U/L vs 66±8 U/L in controls), supporting its incorporation into clinical guidelines for obstructive hepatobiliary disease management, we recommend incorporating hepatoprotectors into standard treatment protocols for patients presenting with obstructive diseases of the hepatobiliary system.